Logixpro Based Scada Simlations Model for Packaging System in Dry ICE Plant - Prashu Jain; K. Nithiyananthan; Raghuraman Raghuraman; Gowrishankar Kasilingam (Institute of Advanced Engineering and Science, 2015)
Supervisory Control and Data Acquisition (SCADA) systems control and monitor industrial and critical infrastructure functions, such as electricity, gas, water, waste, railway, and traffic. The main objective of this work is to develop SCADA simulation model for packaging system in dry ice plant. Dry ice is an important refrigerant for keeping foods cold and preventing bacterial growth during shipment. Dry ice used for cooling or freezing foods must be very clean and considered food grade to ensure that food it may touch will not be contaminated. Some recent developments for its use include using the pellets in blasting or cleaning and its increasing use in transporting medical specimens, including hearts, limbs, and tissues, for reattachment and transplantation. The manufacturing process of dry ice has not changed significantly in many decades and is a relatively simple process of pressurizing and cooling gaseous carbon dioxide. But because of its growing demand, packaging becomes vital. An attempt has been made to develop and automate LOGIXPRO based SCADA simulations for dry ice plant to improve packaging and extensively reduce operating labor costs.